Effectiveness of Rainwater Harvesting Filters using Natural Resources - Ahmad, Nur Izzati; Anak Jose, Joyce Inya; Iskandar , Najiah Husna; Abdul Kadir, Muhammad Azraie (Multidisciplinary Applied Research and Innovation, 2022)
Rainwater harvesting is a collection and storage process of rainwater for daily use such as watering plant and washing the car. Unfiltered contaminant and foreign material from the rainwater cause bacteria growth which will effect users’ health in long run. Moreover, the way the rainwater is collected from the rooftop or disinfect material also allows heavy metal such as zinc to pollute the water supply.  The design of simple water filter is needed to solve these problem with the use of available natural resources around the region such as activated carbon and coconut husk. Rainwater sample from UTHM Pagoh resident rooftop building is collected to investigate the parameter and characteristics of the sample before and after the filtration. In the end, the results should indicate that the pH value of two samples have different value between 6 to 9 and Total Dissolved Solid (TDS) should be between 5 to 7 mg/l based on National Water Quality Standard for Malaysia (NWQSM) requirements. The study offers a handy treatment that can help the users have a clean water from rainwater collection.